The Prevalence of Thyroid Disorders in Pregnant Women of Hamadan - Shiva Borzouei; Mohammad Taghi Goodarzi; Mansooreh Biglari; Fathollah Nazari; Zahra Shivapour (Hamadan University of Medical Sciences, 2019)
Introduction: Different studies have demonstrated that maternal thyroid dysfunction during pregnancy is associated with adverse obstetrics and fetal outcomes. There is no international consensus regarding to use a guidelines for screening in high risk women. The aim of the present study was to determine prevalence of thyroid disorders in high and low risk pregnant women. Methods: In a cross-sectional study during 2015-2016, from all pregnant women who had referred to Hamadan health center Lab for their first visit, a sample of 852 pregnant women were selected and assigned to low risk and high risk group. Thyroid tests and Anti TPO tests were carried out. Results: Of 852 pregnant women, 26.5% had Subclinical hypothyroidism, 1.2% had overt hypothyroidism, 0.5% had overt hyperthyroidism and 0.2% had subclinical hyperthyroidism. 25.6% were in the high risk group and 74.4% in the low risk group and 37.4% of high risk group and 25% of the low risk population had thyroid disorders (P<0/001). 89% were Anti TPO negative and 11% were Anti TPO positive. Conclusion: Hypothyroidism is common in pregnant women, and if screening is performed only in high-risk groups, 25% of pregnant women with subclinical and overt hypothyroidism will not  be detected explicitly. In addition, to determine the exact frequency of thyroid disorders, we need to look for newer and more effective criteria.